Evaluation of Early Graft Detachment After Descemet Membrane Endothelial Keratoplasty Using New Swept-Source Optical Coherence Tomography. Issue 10 (October 2016) - Satue, Maria; Idoipe, Miriam; Sanchez-Perez, Antonio; Liarakos, Vasilis S.; Mateo, Antonio; Garcia-Martin, Elena; Polo, Vicente; Gavin, Alicia; Brito, Carlos
Abstract : Purpose: To evaluate the ability of Swept-source optical coherence tomography (SS-OCT) in detecting early endothelial graft detachment after Descemet membrane endothelial keratoplasty (DMEK) and to determine the possible causes of graft detachment using 2 different protocols for anterior segment (AS) imaging. Methods: Eight eyes from 8 consecutive DMEK surgeries were evaluated. High-resolution images were captured with SS-OCT using 2 different radial protocols for AS imaging (16- and 6-mm radial protocols). Central and peripheral corneal changes were evaluated. Results: All eyes developed early graft detachment detectable with the SS-OCT. The 16-mm radial protocol scanned the cornea detecting early graft detachment in 6 out of 8 cases. The 6-mm radial protocol provided detailed images of the cornea, detecting early detachment in all cases. Stromal irregularities and small remnants only detectable using SS-OCT were the possible cause of detachment in 3 cases. One of the 8 eyes had air reinjection. The detachment in that eye was apparent by slit-lamp examination. The detachments spontaneously resolved in the other 7 eyes. AS SS-OCT evaluation was found to have added diagnostic value to biomicroscopy in 5 of these eyes (64.5%). Conclusions: AS SS-OCT is sensitive in detecting early graft detachment after DMEK. The 16-mm radial protocol of Triton SS-OCT is superior regarding quick scan of the entire cornea providing a general visualization of the DMEK graft. The 6-mm radial protocol provides detailed corneal imaging of a selected area, which is useful for evaluating structural alterations that are not detectable with larger scans and may affect the adherence of the endothelial graft. Abstract : Supplemental Digital Content is Available in the Text.